2020
DOI: 10.3389/fsufs.2020.00106
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Plant Growth Promoting Microbes in Enhancing Plant Tolerance to Acidity and Alkalinity Stresses

Abstract: Plant growth often occurs under a range of stressful conditions, including soil acidity and alkalinity. Hydrogen ion concentration, which determines pH of the soil, regulates the entire chemistry of plant nutrient colloidal solutions. Beyond certain levels of pH, multiple stresses such as hydrogen ion toxicity, and nutrient imbalance, toxicities and deficiencies are induced in plants. Breeding for stress coupled with suitable agronomic practices has been a way to deal with this situation in agriculture. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(117 citation statements)
references
References 129 publications
2
110
0
5
Order By: Relevance
“…Initially, the bacterial isolate MB-17a shows little growth at pH 3, but after attaining pH from 5 to 9, it showed significant growth. It showed that growth increased with a rise in pH, accompanied by a decrease in alkaline pH (Msimbira and Smith, 2020 ). The effect of different pH values on the growth of Rhizobium pusense MB-17a is demonstrated in Figure 2B .…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the bacterial isolate MB-17a shows little growth at pH 3, but after attaining pH from 5 to 9, it showed significant growth. It showed that growth increased with a rise in pH, accompanied by a decrease in alkaline pH (Msimbira and Smith, 2020 ). The effect of different pH values on the growth of Rhizobium pusense MB-17a is demonstrated in Figure 2B .…”
Section: Resultsmentioning
confidence: 99%
“…Besides inoculum density and inoculation method, plant response to PGPM inoculation depends on root colonization, which varies with microorganism's multiplication and distribution through the rhizosphere, microbial antagonism, soil humidity, pH, temperature, host, root exudates, as well as the plant physiological state (Venturi and Keel, 2016;Hernández-Montiel et al, 2017;Msimbira and Smith, 2020). After inoculation, the decrease in microorganism population, may be related to difficulties in adapting to their new environment.…”
Section: Inoculation Methods For the Success Of Plant Growth-promotinmentioning
confidence: 99%
“…The knowledge on physiological characteristics of the microbial inoculant and the host plant is essential to decide the best inoculation method (Strigul and Kravchenko, 2006;Souza et al, 2015;Etesami, 2020). Successful microbial inoculation depends on inoculation method, inoculum density, root colonization, which varies with multiplication and distribution microbes through the rhizosphere, microbial antagonism, plant physiological state, soil humidity, pH, temperature, host, and root exudates (Venturi and Keel, 2016;Hernández-Montiel et al, 2017;Msimbira and Smith, 2020). Microbial inoculants are placed mainly into seeds (Romeiro, 2007;Souza et al, 2015, Arora et al, 2020.…”
Section: Factors That Affect the Success Of Microbial Inoculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of PGPM, as inoculants, in crop production is a common and old practice ( Bashan et al, 2014 ) in many parts of the world, for increased productivity and sustainability ( Babalola and Glick, 2012 ). There is currently a substantial number of promising microbial inoculants, some already on the market ( Velivelli et al, 2014 ; Mehnaz, 2016 ; Berninger et al, 2018 ; Arthur and Dara, 2019 ), with various mechanisms of enhancing crop growth, ranging from growth stimulation, to enhanced defense against pathogens and abiotic stress ( Barea, 2015 ; Gupta et al, 2015 ; Bender et al, 2016 ; Msimbira and Smith, 2020 ; Naamala and Smith, 2020 ). Despite their undisputable success in enhancing crop production ( de Boer et al, 2019 ; Lyu et al, 2020 ), the use of PGPM technology, in crop production, has been constrained by a number of limitations, most notably, inconsistencies, especially under field conditions.…”
Section: Introductionmentioning
confidence: 99%